Emerging technological innovation in Gaza Strip municipalities: An entrepreneurial approach - Ashraf Y. AlAstal (Journal of Innovation and Entrepreneurship, 2023)
To boost corporate efficiency in both the public and private sectors, innovation is fundamental. Efficient technological transfer and the role of public-private sector collaboration play a major role in the modern growth of knowledge-based economies. As a public service organization, municipalities normally coordinate with all partners to draw up strategies and use them in communities. A new vision is needed for the Gaza Strip municipalities, where all public and private stakeholders work together to co-design and co-develop new cutting-edge products and services aimed at generating shared value through entrepreneurial behavior. However, concrete examples of smart city projects revealed that municipalities often do not have the necessary capabilities as well as innovative approaches to collaborate with start-ups and other stakeholders' ecosystems. So, this paper aims to analyze innovation in the municipal sector shedding light on the barriers and challenges that municipalities in the Gaza Strip face in smart city development. This study uses primary data gathered from various stakeholders through focus groups, semi-structured interviews, and webinars to conclude how the Gaza Strip municipalities can work to address challenges in the smart city context; and to explore how to promote an ecosystem of entrepreneurship and innovation to support the adoption of new hi-tech technologies in the municipal sector. The Gaza Strip municipalities need to offer the necessary conditions for entrepreneurial talents who can bring their creative mindset, and technological experiences to the table, making it possible to build the best teams to solve any challenge. The research also concluded that Open Innovation Platforms can be seen as an important tool for enabling start-ups and researchers to develop innovative Hi-Tech solutions.
Keywords: 650; Entrepreneurship; Open innovation; Municipalities; Emerging technologies; Public sector; Technological start-ups